Implementasi Model Pembelajaran Search, Solve, Create And Share (Sscs) Untuk Meningkatkan Kemampuan Berpikir Kreatif Matematis Dan Dampaknya Terhadap Disposisi Matematis Siswa SMA - Ningsih, Eva Fitria (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2015)
Themainpurpose of this resaerch was to conduct a study focusing on the use SSCS model is assumed capable to increase students mathematical creative thinking abilityand see the impact on mathematical disposition, based on student of all and Prior Mathematical Ability (PMA) students (high and low). The method of this research is a mixed methods type of Embedded Design. The population of thisresearch is X graders of SMA Pasundan 3 Bandung, and the samples are the students in X-1 as the experimental group and student in X-2 as the control group. Thisresearch used two kinds of instruments: PMA test, mathematical creative thinking ability test, mathematical disposition scale, observation sheet and interview. This research used Independent Sample t-Test and Two-Way ANOVA. Conclusion of this research are: 1) based on students of all, the enhancement mathematical creative thinking ability of students who were given SSCS model are better than students who were given expository learning. When based on PMA category , increase mathematical creative thinking ability of students high and low who were given SSCS model are better than students who were given expository learning; 2) based on students of all, the enhancement mathematical disposition of students who were given SSCS model are better than students who were given expository learning. When based on PMA category , increase mathematical disposition of students high and low who were given SSCS model are better than students who were given expository learning; 3) Mathematical disposition to support the successof learning mathematics, in this case the mathematical creative thinking ability.. Students who have high disposition to be more persistent, persevere and interested to explore new things. This Allows students to have more knowledge than the students who did not show such behavior. Knowledge is what causes students to have Certain abilities. 4) There is a positive impact on the mathematical creative thinking ability of student to mathematical disposition